Green solutions for removing and storing carbon in urban districts - Fabrizio Tucci; Marco Giampaoletti (Agathón)
This paper presents the research developments arising from the study of more than 100 tree and shrub species present in the Mediterranean basin according to their carbon absorption and storage capacities, defining an overview of use for parties active in the sector. The introduction of specific taxonomic storage indices defines the experimental phase performed in a public housing neighbourhood in Rome, illustrating a proposed urban reforestation project integrated with the overall one for regenerating the entire area of Italy’s Capital. The issue is of great scientific importance in light of the national and European strategies and policies contained respectively in the National Recovery Plan and the proposed New EU Forest Strategy – Fit for 55, currently pending in the European Parliament.